2020
DOI: 10.1039/c9nr09137h
|View full text |Cite
|
Sign up to set email alerts
|

Effective replacement of cetyltrimethylammonium bromide (CTAB) by mercaptoalkanoic acids on gold nanorod (AuNR) surfaces in aqueous solutions

Abstract: The highly packed cetyltrimethylammonium bromide bilayer on the surface of gold nanorods synthesized by the seed-mediated procedure hampers the complete ligand exchange under experimental conditions that preserves the stability of the dispersions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…It is a well-known strong interaction 44,45 , which has been used, for instance, to control the morphology and shape of gold nano-structures [45][46][47][48][49] . A special feature of the CTAB-gold interaction, rst proposed by El-Sayed et al 45 and con rmed by numerous subsequent studies, is the formation of an adsorbed CTAB double layer on the gold surface 45,50,51 . The proposed structure of that bilayer is the following (Fig.…”
Section: The Relevant Interactions In the Gox-ctab-gold Systemmentioning
confidence: 87%
“…It is a well-known strong interaction 44,45 , which has been used, for instance, to control the morphology and shape of gold nano-structures [45][46][47][48][49] . A special feature of the CTAB-gold interaction, rst proposed by El-Sayed et al 45 and con rmed by numerous subsequent studies, is the formation of an adsorbed CTAB double layer on the gold surface 45,50,51 . The proposed structure of that bilayer is the following (Fig.…”
Section: The Relevant Interactions In the Gox-ctab-gold Systemmentioning
confidence: 87%
“…It is believed that effective biopolymer protection of nanoparticles should prevent the aggregation process via electrostatic or steric repulsion [10][11][12]. However, the 10:1 ratio result showed a different outcome as they are less stable in PBS (pH 7.4).…”
Section: Stability Of Gelatin@au-nrs In Biological Mediamentioning
confidence: 99%
“…However, studies have shown that it is one major cause of AuNRs toxicity [6][7][8][9]. Therefore, it is essential to find biocompatible, non-toxic, and stable surface modifying agents to passivate Au-NRs and reduce their toxicity whilst maintaining their optical properties [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Cetyltrimethylammonium bromide (CTAB) is the most commonly used surfactant and can form rod-shaped micelles in solution, which can effectively control the directional growth of anisotropic nanomaterials and promote the formation of NRs. In this mode, the CTAB acts as both a template and coating agent, facilitating mass production of NRs and nanowires [57,58]. Khanal et al developed a reversible chemical process for tip selective one-dimensional growth and dissolution of AuNRs, which can be continued with additional supply of Au(I)/CTAB/ascorbic acid solution to produce extremely long Au nanowires [59] (Figure 3).…”
Section: Nanorods (Nrs)mentioning
confidence: 99%